2020
DOI: 10.5858/arpa.2020-0070-ra
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Manifestations of Gastrointestinal and Hepatobiliary Injury in Immune Checkpoint Inhibitor Therapy

Abstract: Context.— Immune checkpoint inhibitors (CPIs), including cytotoxic T-lymphocyte–associated protein 4 (CTLA-4) inhibitors and the programmed death receptor-1 (PD-1)/programmed death ligand-1 (PD-L1) inhibitors, are being increasingly used for treating many advanced malignancies. However, CPI therapy is also associated with gastrointestinal and hepatobiliary adverse effects. Objectives.— To review the adverse effects of CPI therapy on the gastrointestinal tract and hepatobiliary system. To describe histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 69 publications
(163 reference statements)
3
52
0
Order By: Relevance
“…CD n (%) Control n (%) CD8 + T cells are the effectors of ICI anti-tumour effects, and high levels of CD8 + T cell infiltration in tumours before and during ICI treatment are associated with improved ICI efficacy [23]. The extent of CD8 + T cell mucosal infiltration in CIC reported in this study is comparable to heavy CD8 + T cell infiltration previously described in non-intestinal sites of autoimmune inflammation [24][25][26][27].…”
Section: Discussionsupporting
confidence: 76%
“…CD n (%) Control n (%) CD8 + T cells are the effectors of ICI anti-tumour effects, and high levels of CD8 + T cell infiltration in tumours before and during ICI treatment are associated with improved ICI efficacy [23]. The extent of CD8 + T cell mucosal infiltration in CIC reported in this study is comparable to heavy CD8 + T cell infiltration previously described in non-intestinal sites of autoimmune inflammation [24][25][26][27].…”
Section: Discussionsupporting
confidence: 76%
“…The anti-PD-1 antibodies, such as nivolumab and pembrolizumab, have been successfully used to treat patients with multiple advanced malignancies. 25 The histologic patterns of hepatic toxicity induced by anti-PD-1 treatment have not been well studied 25,27 but anti-PD-1 therapy-induced steatohepatitis has been reported by our group. 25 Specifically, a steatohepatitic pattern (Figure 2, D) of injury was observed in 1 of 8 cases in our study.…”
Section: Immunotherapy-induced Steatosis and Steatohepatitismentioning
confidence: 91%
“…It should be noted that a lymphocyte-predominant oesophagitis can also be associated with the use of check-point inhibitor therapy. 70…”
Section: L I N I C a L F E A T U R E Smentioning
confidence: 99%
“…Multiple studies have also demonstrated an association between smoking and the risk of LO, 58,61,69 although the underlying mechanism for this remains unclear. It should be noted that a lymphocyte‐predominant oesophagitis can also be associated with the use of check‐point inhibitor therapy 70 …”
Section: Lymphocytic Oesophagitis (Lo)mentioning
confidence: 99%